Legal Analysis of PPP Regulations on Investor Flexibility in Undertaking Corporate Actions: A Case Study of the Trans Papua Road PPP Project (JayapuraWamena Section) - Adi Satria, Kun Hartawan; Rifai, Anis (Riwayat: Educational Journal of History and Humanities, 2025)
Public-Private Partnership (PPP) schemes, known in Indonesia as Kerja Sama Pemerintah dengan Badan Usaha (KPBU), have become a strategic solution for infrastructure development, yet they still face regulatory challenges, particularly regarding investor flexibility in undertaking corporate actions. This study examines the legal aspects of KPBU regulations on investor flexibility through a case study of the Trans Papua Road Project, JayapuraWamena section. The research employs a normative-empirical legal method with a qualitative approach, analyzing KPBU regulations, project contract provisions, and international comparative practices. The findings indicate that KPBU regulations provide legal certainty and a risk-sharing framework but continue to restrict investor flexibility due to rigid contractual obligations and mandatory approvals from the government contracting agency (PJPK). The Trans Papua case demonstrates that while contractual clauses ensure legal certainty, they also limit corporate maneuverability. This study recommends harmonizing KPBU regulations with corporate law to strengthen legal certainty while accommodating greater investor flexibility.